ORAL CAVITY SQUAMOUS CELL CARCINOMA IN A CASE OF IFAP SYNDROME WITH CHRONIC MYELOID LEUKEMIA ON LONG TERM HYDROXYUREA: A RARE PRESENTATION - P, Uday Kumar; Singh, Anshul; Reddy s, Anusha; VIDYASGAR MS; Prahlad Hy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
We report a case ofÂ a patientÂ in his earlyÂ 30s' who presented with an ulcero-proliferative growth over the left buccal mucosa , he was also on treatment for CML in blast crisis on Hydroxyurea and a known case of Ichthyosis Follicularis, Alopecia, and Photophobia (IFAP) syndrome. Though a working diagnosis of chloroma / Hydroxyurea induced erosive Lichen planusÂ was suspected, the histopathological examination of the lesion was suggestive of Squamous cell Carcinoma. He was subsequently planned for palliative radiotherapy . Â